Fragilidade ambiental e expansão urbana da região administrativa nordeste da sede do município de Santa Maria - RS - Nascimento, Marilene Dias do (2009)
Over the past decades, the degradation of natural resources is a constant reality in the cities of Brazil and has been creating environmental and social concern. Geomorphological studies help to understand these environmental problems, since it deals with the interaction of complex mechanisms that modify the surface of the globe. And the study of natural environmental fragility, exacerbated by human activities in urban environments, should be the subject of research aimed at the urban sprawl. The objective of this research is to diagnose the potential and emerging environmental fragility of the Northeast Administrative Region of the Municipality of Santa Maria-RS, which corresponds to the transition zone between the Southern Rio Grande Peripheral Depression and the Plateau of the Paraná Basin, with high altimetric amplitude and steep slopes. The methodology used is based on Ross (1994), in which environmental fragility is defined by the concepts of Ecodynamic Units (Tricart, 1977), grouped in Unstable Ecodynamic Units and Stable Ecodynamic Units, with the establishment of degrees of fragility rated from very low, for the least degree, to very high for the greatest degree. The Potential Environmental Fragility Chart resulted from the overlay of Information Planes (IPs) of the Clinographic, Morphological, Geologic and Soils Charts. The Chart of Emerging Environmental fragility is the result of the overlay of IPs Potential Environmental Fragility Chart with the Land Use and Land Cover Charts. These charts show the different degrees of fragility that the environment has on the basis of their genetic and anthropic characteristics. In the Potential Environmental Fragility Chart, it was found that 42.9% of the present environmental fragility rated high to very high. These vulnerabilities occur due to the physical properties of places with the large terrain slopes, combined with low soil development and hill morphology. The analysis of human intervention appears that the environmental fragility increases considerably. The Chart of Emerging Environmental Fragility reveals that 79.2% of the study area are considered fragile medium to very high, and 48.6% have a high fragility. The areas of greatest fragility are those that are least protected, or those where there have been much modification of the natural environment resulting from human actions. In this regard, some recommendations were proposed in order to modify land use so that the Northeast Administrative Region can remain in environmental balance. And finally, it should be noted that this research lends itself as an aid to future work that may be developed in the area, especially those focused on environmental preservation.